2019
DOI: 10.1016/j.applthermaleng.2019.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Staged oxy-fuel natural gas combined cycle

Abstract: Exhaust gas recirculation (EGR) in conventional natural gas-fired oxy-combustion cycles is required to maintain the combustion temperature at an allowable level. However, EGR is not beneficial from the system performance perspective. It is difficult to achieve in oxy-fuel cycles due to the high pressure and increased pressure drop in such systems. Consequently, alternative options to control the combustion temperature need to be considered. In this study, staged oxy-fuel natural gas combined cycle (SOF-NGCC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The considered BOXS-CC process consists of a syngas gasification section and two power generation sections: (1) the staged oxy-combustion power cycle and (2) the sCO2 cycle. The power generation sections have been previously validated and investigated extensively by Khallaghi et al [19,21]. The accuracy of the gasification model used in this study is validated based on the wood chip oxy-gasification reported by Dimitriou et al [33].…”
Section: Model Validationmentioning
confidence: 97%
See 2 more Smart Citations
“…The considered BOXS-CC process consists of a syngas gasification section and two power generation sections: (1) the staged oxy-combustion power cycle and (2) the sCO2 cycle. The power generation sections have been previously validated and investigated extensively by Khallaghi et al [19,21]. The accuracy of the gasification model used in this study is validated based on the wood chip oxy-gasification reported by Dimitriou et al [33].…”
Section: Model Validationmentioning
confidence: 97%
“…To improve the performance of the BOXS-CC system, a sensitivity analysis was performed on the split fraction ( ) in the sCO2 cycle, gasification temperature and combustion temperature. It is worth noting that the effects of the pressure and temperature in the sCO2 cycle have been extensively analysed in the literature [19,21].…”
Section: Thermodynamic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Here, endothermic reforming utilizes the sensible heat of combustion products and can be formally represented using one partial oxidation reactor, as shown in Figure 4 . Compared to the staggered oxy-fuel combustion in some consecutive chambers where oxygen and fuel are distributed in a way to reach maximum admissible temperature in each chamber, followed by an interstage heat transfer “through the wall” to water 17 or supercritical CO 2 , 18 the staggered combustion shown in Figure 5 is controlled by the catalytic endothermic reaction accepting combustion products as its reactants. Both methods help in reducing the recirculation of exhaust gases (combustion products) per unit of released heat to control the maximum combustion temperature, resulting in a more compact unit without loss in efficiency.…”
Section: Integrated Gtu For Power and Syngas Cogenerationmentioning
confidence: 99%